2014
DOI: 10.1371/journal.pone.0091208
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Reversal in European Whitefish (Coregonus lavaretus (L.)) Caused by Competitor Invasion

Abstract: Invasion of exotic species has caused the loss of biodiversity and imparts evolutionary and ecological changes in the introduced systems. In northern Fennoscandia, European whitefish (Coregonus lavaretus (L.)) is a highly polymorphic species displaying adaptive radiations into partially reproductively isolated and thus genetically differentiated sympatric morphs utilizing the planktivorous and benthivorous food niche in many lakes. In 1993, Lake Skrukkebukta was invaded by vendace (Coregonus albula (L.)) which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 80 publications
(114 reference statements)
3
54
0
Order By: Relevance
“…This has resulted in hybridization between the invasive species and native whitefish in certain lakes (Kahilainen et al., 2011). In other lakes, competitive exclusion of native densely rakered whitefish species by the invasive has occurred, combined with massive introgression and the loss of phenotypic and genetic differentiation between the previously distinct densely rakered and large sparsely rakered whitefish species (Bhat et al., 2014). Alternatively, neutral models of coexistence (Leibold & McPeek, 2006), potentially followed by ecological character displacement or specialization within the shared niche, buttressed by the nonoverlap of spawning habitats between these species could allow the persistence of both species.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in hybridization between the invasive species and native whitefish in certain lakes (Kahilainen et al., 2011). In other lakes, competitive exclusion of native densely rakered whitefish species by the invasive has occurred, combined with massive introgression and the loss of phenotypic and genetic differentiation between the previously distinct densely rakered and large sparsely rakered whitefish species (Bhat et al., 2014). Alternatively, neutral models of coexistence (Leibold & McPeek, 2006), potentially followed by ecological character displacement or specialization within the shared niche, buttressed by the nonoverlap of spawning habitats between these species could allow the persistence of both species.…”
Section: Discussionmentioning
confidence: 99%
“…Other Delphinus populations may be at a different stage in the process, in an environment where isolation is less strongly promoted, or even represent the collapse of a previous pattern of differentiation (for example, as seen for whitefish, Coregonus lavaretus; Bhat et al, 2014). Chance events associated with founder size and the extent of genetic drift, or differences associated with environmental conditions or local processes, may be relevant to the differential extent of isolation in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…The whitefish from Stuorajávri were significantly more advanced in sexual maturity than the whitefish from Suohpatjávri. Hybrids between whitefish ecomorphs frequently occur in all northern Fennoscandian lakes, but genetic studies have only observed hybridisation between DR-LSR whitefish (Bhat et al, 2014) and between LSR-SSR whitefish (Praebel et al unpublished). We also found, in both lakes, that male and female DR and male LSR whitefish displayed a similar state of maturity, while the female LSR and male and female SSR whitefish were less mature.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our own field observations, information from locals and the presence of hybrids between the ecomorphs (Bhat et al, 2014), it seems that all three ecomorphs mainly share the same spawning ground(s) in the littoral zone, and with the knowledge of whitefish ecomorphs' thermal niches, we hypothesised that differences in spawning time (allochrony) acts as the main driver of reproductive isolation. The challenge of revealing reproduction in these northern systems, compared with more southern lakes for example in Sweden, Denmark and the European Alps, is that the spawning takes place in late October to December, when the lake ice is too thin to work on, but too thick for boating.…”
mentioning
confidence: 99%
See 1 more Smart Citation